2011
DOI: 10.1097/inf.0b013e3182154b05
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem/Clavulanate and Linezolid Treatment for Extensively Drug-resistant Tuberculosis

Abstract: The combination of meropenem with clavulanate has high antimycobacterial activity in vitro against extensively drug-resistant Mycobacterium tuberculosis strains. We report the successful use of this combination in association with linezolid in the management of an advanced extensively drug-resistant tuberculosis disease with complex second-line drug resistance in a 14-year-old teenager.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Although encouraging results have recently been obtained using meropenem for the treatment of XDR-TB in humans (18)(19)(20), the instability and poor bioavailability of this compound, which necessitate frequent or continuous intravenous administration, will likely restrict its broader clinical application. Faropenem is an orally bioavailable penem antibiotic that is more resistant to hydrolysis by ␤-lactamases than cephalosporins and carbapenems are (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although encouraging results have recently been obtained using meropenem for the treatment of XDR-TB in humans (18)(19)(20), the instability and poor bioavailability of this compound, which necessitate frequent or continuous intravenous administration, will likely restrict its broader clinical application. Faropenem is an orally bioavailable penem antibiotic that is more resistant to hydrolysis by ␤-lactamases than cephalosporins and carbapenems are (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of conventional animal models to obtain proof of in vivo efficacy for ␤-lactams is problematic due to rapid enzymatic hydrolysis by dehydropeptidase, which is more active in mice, rats, pigs, and rabbits than humans (17,47,48). This issue is exemplified by studies of meropenem, which has been successfully used for the treatment of human tuberculosis in clinical cases (18)(19)(20), despite exhibiting marginal bactericidal activity when tested in mice (15,40). In the mouse model, we found that faropenem alone does not reduce bacterial loads in the lungs of treated mice compared to those in the lungs of untreated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the combination of clavulanic acid with meropenem was found to be highly effective against XDR isolates of M. tuberculosis (12). Moreover, the use of meropenem and clavulanic acid as part of a salvage regimen was recently reported to show promising results (13). Unfortunately, meropenem must be delivered intravenously, thereby limiting its widespread use as prolonged therapy.…”
mentioning
confidence: 99%
“…Another study showed that treatment of TB patients with an amoxicillin/clavulanate combination significantly reduced M. tuberculosis counts with early bactericidal activity comparable to patients treated with the frontline drug INH (Chambers et al, 1998). Importantly, a case report recently described the successful recovery of an advanced XDR-TB patient treated with meropenem/clavulanate in conjunction with other drugs (Dauby et al, 2011). In summary, evidence obtained from numerous studies performed in vitro, in animals, and in humans, all support that lactams potentiated by lactamase inhibitors could provide an effective addition to the treatment of drug resistant TB.…”
Section: Potentiation Of Lactams In Mycobacteriamentioning
confidence: 99%